IMPLEMENTASI PEMBELAJARAN SEJARAH DENGAN TEKNIK KONTEKTUAL COMMUNITY UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS XII/IPS.4 SMAN 1 KERTOSONO NGANJUK - Sawin (Jurnal Pendidikan Islam, 2019)
Abstract: Learning History in SMAN 1 Kertosono Nganjuk in its implementation still leaves various problems. The majority of learning methods so far are more emphasized on memorization which results in that students lack understanding of the uses and benefits of what has been learne d and cause a decrease in student motivation. One alternative that can be used is the application of contextual learning with Community Learning techniques. With the use of this technique, it is hoped that History subjects can be easily understood and can increase student motivation and learning achievement. Departing from the above problems, in general the problems formulated in this study are 1) How is the motivation and learning achievement of the history of class XII / IPS.4 students before applying con textual learning to the Learning Community technique? 2) How is the contextual learning implementation with the Learning Community technique in increasing motivation and learning achievement History, 3) How is the motivation and learning achievement Histor y of class XII / IPS students.4 SMAN 1 Kertosono Nganjuk after applying contextual learning with the Learning Community technique? This research was conducted at SMAN 1 Kertosono Nganjuk. This research is a class action research with collaborative type. Th is research phase follows the Kemmis and Taggart models which include planning, implementing actions, observing, and reflecting activities. Data collection techniques used are: (1) observation; (2) measurement of learning outcomes tests; and (3) documentat ion. The results of the research that have been carried out that 1) Research teachers carry out pre - cycle learning by applying lecture and test methods. 2) Implementation of Contextual Learning with Community Learning Techniques on the History of Class XII / IPS.4 Student History is carried out with 3 cycles consisting of 6 meetings. During the learning process observations are carried out to determine student motivation and at the end of the cycle a final test is carried out to determine student learning o utcomes. 3) Student's motivation and learning achievement towards History through contextual learning with Learning Community techniques has increased student learning motivation from pre - research by 14.29% to 17.14% in cycle I and in cycle II to 22.14%. I n cycle III it increased to 32.14%. The increase in learning outcomes at the time of pre - study average class of 65.74 increased in the first cycle to 66.48. In cycle II it increased to 73.16 and in cycle III it increased to 82.04. Likewise the completeness of the Annaba : Jurnal Pendidikan Islam Volume 5 No. 2 , 1 September 2019 Sawin 202 Annaba : Jurnal Pendidikan Islam class at the time of the pre cycle by 37.04% increased to 51.85% in the first cycle and increased in the second cycle to 70.37% and in the third cycle increased to 88.89%